A Counterattack-Detection Scheme in Transmission Time-Based Wormhole Detection Methods. (31st March 2013) - Kim, Dong-uk; Kim, Hyo-won; Kim, Gisung; Kim, Sehun
Abstract : In recent years, the Mobile Ad hoc Network (MANET) is getting more important and is being utilized in various fields. However, routing-disruption attacks have become a serious problem for MANET. In various routing-disruption attack detection methods, transmission time-based methods can detect wormhole attacks efficiently. Attackers might fabricate a time stamp for a Route Request Packet (RREQ) or Route Reply Packet (RREP) to evade wormhole detection methods. To resolve this weakness, we propose a counterattack-detection scheme in transmission time-based wormhole detection methods. In this paper, we show that it is possible for an attacker to find an effective counterattack against wormhole detection methods, so we provide a counterattack-detection scheme. In the first phase, our proposed method uses the transmission time per hop extracted from a RREQ. If the attackers fabricate the RREQ's starting time to evade our proposed method, we can detect this counterattack using the RREQ's transmission time in the second phase, because the fabricated starting time makes the transmission time shorter than the original transmission time. The simulation shows that our proposed method has high reliability for detecting both wormhole attacks and the attacker's counterattack.